Internalized HIV/AIDS-related stigma in a sample of HIV-positive people in Bangladesh - Hasan, Tanvir; Nath, Samir Ranjan; Khan, Nabilah S.; Akram, Owasim; Gomes, Tony Michael; Rashid, Sabina Faiz (© 2012 International Centre for Diarrhoeal Disease Research, Bangladesh., 2017)
This article was published in the Journal of Health, Population and Nutrition [ © 2012 International Centre for Diarrhoeal Disease Research, Bangladesh. ] and The Journal's website is at: http://www.jstor.org/stable/23500101